The Role of Semaphorin 4D in Bone Remodeling and Cancer Metastasis - Lontos, Konstantinos; Adamik, Juraj; Tsagianni, Anastasia; Galson, Deborah L.; Chirgwin, John M.; Suvannasankha, Attaya (Frontiers in Endocrinology, 2018)
Semaphorin 4D (Sema4D; CD100) is a transmembrane homodimer 150-kDa glycoprotein member of the Semaphorin family. Semaphorins were first identified as chemorepellants that guide neural axon growth. Sema4D also possesses immune regulatory activity. Recent data suggest other Sema4D functions: inactivation of platelets, stimulation of angiogenesis, and regulation of bone formation. Sema4D is a coupling factor expressed on osteoclasts that inhibits osteoblast differentiation. Blocking Sema4D may, therefore, be anabolic for bone. Sema4D and its receptor Plexin-B1 are commonly dysregulated in cancers, suggesting roles in cancer progression, invasion, tumor angiogenesis, and skeletal metastasis. This review focuses on Sema4D in bone and cancer biology and the molecular pathways involved, particularly Sema4D–Plexin-B1 signaling crosstalk between cancer cells and the bone marrow microenvironment—pertinent areas since a humanized Sema4D-neutralizing antibody is now in early phase clinical trials in cancers and neurological disorders.